FRIEDMAN'S ANALYSIS OF THE READING LITERACY PROGRAM IN IMPROVING STUDENT'S READING SKILLS - Pitri, Rizka Pitri; Alvionita, Elisya (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2025)
The School Literacy Movement (GLS) is an effort to cultivate character through reading activities. GLS becomes the foundation of the learning process through the establishment of a school culture as a comfortable learning environment and leads to increased literacy skills in students. One of the School Literacy Movement is the 15-minute reading program before learning begins which is implemented in education units. However, the GLS program has not been comprehensively based on the GLS guidelines from MoEC-Ristek. The intensity of GLS activities is still lacking because it is only done twice a week. Based on this fact, the researcher conducted a 15-minute reading program before learning begins four times a week. This study aims to evaluate the implementation of the reading literacy program in improving reading skills. The samples in this study were early grades I and II of MIN 3 Bandar Lampung. This study used quantitative methods by applying Friedman and Effect Size analysis. This study found that there is a difference in the level of reading skills before and after the implementation of the 15-minute reading program before learning begins, in other words, the program has effectiveness in improving reading skills. The effectiveness of the 15-minute reading literacy program before learning begins on improving the reading skills of early grade students is 0.7 or equivalent to 76% effectiveness.